68Ga‐DOTATATE PET and functional imaging in pediatric pheochromocytoma and paraganglioma. Issue 8 (29th April 2022) - Krokhmal, Aleksandra A.; Kwatra, Neha; Drubach, Laura; Weldon, Christopher B.; Janeway, Katherine A.; DuBois, Steven G.; Kamihara, Junne; Voss, Stephan D.
Abstract: Pheochromocytoma and paraganglioma (PPGL) are rare neuroendocrine tumors in childhood. Up to 40% of PPGL are currently thought to be associated with a hereditary predisposition. Nuclear medicine imaging modalities such as fluorodeoxyglucose positron emission tomography ( 18 F‐FDG PET), 68 Ga‐DOTATATE PET, and 123 I‐metaiodobenzylguanidine ( 123 I‐MIBG) scintigraphy play an essential role in the staging, response assessment, and determination of suitability for targeted radiotherapy in patients with PPGL. Each of these functional imaging modalities targets a different cellular characteristic and as such can be complementary to anatomic imaging and to each other. With the recent US Food and Drug Administration approval and increasing use of 68 Ga‐DOTATATE for imaging in children, the purpose of this article is to use a case‐based approach to highlight both the advantages and limitations of DOTATATE imaging as it is compared to current radiologic imaging techniques in the staging and response assessment of pediatric PPGL, as well as other neuroendocrine malignancies.